Water Transit Time Explains the Concentration, Quality and Reactivity of Dissolved Organic Carbon in an Alpine Stream - G. Grandi; N. Catalán; S. Bernal; C. Fasching; T. I. Battin; E. Bertuzzo (Water Resources Research)
Abstract The amount and quality of dissolved organic carbon (DOC) exported from terrestrial to riverine ecosystems are critical factors influencing aquatic metabolism and ecosystem health in streams, rivers, and lakes. This study investigates the interplay between hydrologic conditions and DOC dynamics in an alpine catchment, focusing on how DOC concentration and quality shift during baseflow, snowmelt, and storm events. Such dynamics were explored in the Oberer Seebach basin (Austria) where sub‐daily DOC concentration data, along with high resolution excitation‐emission matrices and absorbance spectra, were used to characterize DOC concentration and quality. We quantitatively linked hydrologic pathways with DOC dynamics by advancing a framework that couples water age, which tracks the time water spends within the catchment, with the Reactivity Continuum model, which quantifies the evolution of DOC reactivity and ensuing concentration. Results show that simulating both water age and DOC reactivity effectively reproduces DOC concentrations and reveals a correlation between modeled reactivity and observed DOC quality indices. During snowmelt and storm events, rapid hydrologic pathways transport reactive DOC with a quality profile similar to that of freshly formed terrestrial DOC, while during baseflow, slower pathways carry less reactive DOC with a signature of preceding degradation processes. These findings shed light on the role of catchment hydrology in carbon cycling and on its implications for riverine ecosystem functioning.